Experimental studies on flow and heat transfer characteristics of secondary refrigerant-based CNT nanofluids for cooling applications. Issue 3 (23rd February 2020) - Baskar, S.; Chandrasekaran, M.; Vinod Kumar, T.; Vivek, P.; Ramasubramanian, S.
ABSTRACT: The aim of the research work is to explore the convective heat transfer coefficient characteristics of propanol-based nanofluids for cooling applications. The stable suspension of the nanofluid with volume fractions of 0.15 and 0.3 is prepared and characterised. The measurement on the density shows that there is only a negligible increase in the density of the nanofluid and the specific heat of the nanofluid increases with the volumetric concentration of nanofluids. Furthermore, there is an enhancement in the convective heat transfer coefficient of 70% for the nanofluid containing 0.3% of CNT. Abbreviations: CNT: carbon nanotubes; IPA: isopropyl alcohol; MWCNT: multi-walled carbon nanotubes; SDBS: sodium dodecyl benzene sulphate